Association between life course social determinants of health and metabolic syndrome among female secondary school teachers in Johor / Mohammad Fadzly Marzuki - Mohammad Fadzly, Marzuki (2021)
Metabolic syndrome, a cluster of multiple risk factors, is known to increase the risk of cardiovascular diseases, diabetes, and certain cancers. Poor health behaviours such as poor dietary intake and physical activities are known risk factors of metabolic syndrome. However, very little is known if the social determinants of health throughout the lifecourse are associated with metabolic syndrome. The study aimed to explore the association between life-course social determinants of health and metabolic syndrome. The cross-sectional study involved female secondary school teachers living in the state of Johor, Malaysia. The study used available data from the Clustering of Lifestyle risk factors and understanding its association with Stress on health and wellbeing among school teachers in Malaysia (CLUSTer) project by the which was collected in 2013 (visit I). The data extracted were adulthood social determinants of health data (sociodemographic, menopausal and nulliparous, marital status, depression, anxiety and stress scale (DASS 21), fasting blood sugar and fasting lipid profile (triglyceride, lowdensity lipoprotein, and high-density lipoproteins), and anthropometric measurements (abdominal circumference, height and weight). Additional data of childhood social determinant of health were collected by the researcher using a questionnaire survey form by visiting the participants in 2017 (visit II). Childhood components comprised parent’s socioeconomic status, ownership of car and houses, individual childhood health status, housing aspect, negative life events, and birth weight. Latent class analysis (LCA) was used to classify the childhood social determinants of health. The association between metabolic syndrome and social determinants of health was assessed using a weighted multiple logistic regression modelling. LCA was done using MPlus version 7 and iv multiple logistic regression modelling was done using Stata MP 15. A total of 1,185 female participants were included in the analyses. Older than 30 years (30-39: OR: 2.25, 95%: 1.02, 4.98; 40-49: OR 4.32, 95% CI: 1.98, 9.46; 50 and above: OR: 6.33, 95% CI: 2.65, 15.14), Malays (OR: 2.83; 95% CI: 1.31, 6.12) and Indians (OR: 4.73; 95% CI: 1.70, 13.15) when compared to Chinese, widowed and divorced (OR: 4.29; 95% CI: 1.06, 17.32), women with no children (OR: 2.08; 95% CI: 1.32, 3.27) and living in overcrowded house during early childhood (OR: 2.45 95% CI: 1.37, 4.38) had increased odds of metabolic syndrome in the model. The clustered childhood social determinant of health class for both each and whole childhood periods were not associated with metabolic syndrome. Preventing metabolic syndrome did not only involve addressing health behaviour. Emphasis should be given to groups that may have experienced adverse life-course social determinants of health. Keyword: Metabolic syndrome, social determinants of health, structural, intermediary, determinants, life-course, intergenerational, latent class analysis.